Reporting of Mosaics as High-level and Low level mosaics makes more number of embryos available as alternatives for transfer when no euploid embryos are available. (April 2019) - Sawarkar, Sarthak; Shanmugam, Avinash; Ribustello, Lia; Colls, Pere; Large, Mike; Munne, Santiago; Griffin, Darren
Abstract : Introduction: It is relatively common for human preimplantation embryos produced during the course of IVF treatments to contain two or more cytogenetically distinct cell lines. This phenomenon, known as chromosomal mosaicism, can result in either a mixture of euploid and abnormal cells, or abnormal cells bearing distinct chromosomal gains and losses. NGS allows mosaicism to be detected with much greater sensitivity than earlier preimplantation genetic testing (PGT-A) methods. The application of NGS to trophectoderm biopsies, taken from embryos before transfer to the uterus, has provided insight into the clinical impact of mosaicism. However, because some mosaic embryos are have produced successful pregnancies, it may be appropriate to consider transfer of mosaic embryos in the absence of fully euploid embryos and following patient counseling. Materials and Methods: Samples were amplified by SurePlex, sequenced with VeriSeq PGS assay (Illumina) on MiSeq (Illumina) and analyzed with BlueFuse Multi analysis (Illumina). Embryos with at least one fully aneuploid chromosome or one fully aneuploid chromosome and one mosaic chromosome were called aneuploid. Embryos with 3 chromosome abnormalities were designated complex abnormal. Mosaicism was reported when embryos had 20-80% abnormal sequencing profiles. Embryos with low degrees of mosaicism in sequencing profiles were designated as 'Low –Level Mosaics'. When embryos had high degree of mosaicism, they were reported as 'High- Level Mosaics'. Design: Retrospective analysis of PGS procedures involving TE biopsy and NGS performed by laboratories serving over 250 fertility clinics over three years. A total of 3951 embryos resulting from 952 IVF cycles were analyzed. Results: Gross aneuploidy (includes complex abnormals and polyploidies) rates in egg donors (n=402) was 25.62%. Euploid rate in egg donors was 51.00%. 20.90% embryos from egg donors were mosaic, with 11.94% being classified as High-level mosaic and 8.96% being classified as Low-level mosaic. In the non-egg donor group (n=3, 545 embryos) aneuploidy (includes complex abnormals and polyploidies) ranged at 44.23%. Euploid rate in non-egg donors was about 36.47%. About 15.94% embryos were mosaic with no trend observed in advanced maternal age and mosaicism. About 8% of all embryos in the non-egg donor group were High-level mosaics while and equal percentage of embryos were Low- level mosaics. A total of 33% cycles (n=317 cycles) resulted in cohorts which had zero euploid embryos. Of these 317 cycles however, 112 cycles (35%), had at least one mosaic embryo to transfer. Of the zero-euploid group a total of 52 cycles (16%) resulted in a Low-level mosaic for patients who otherwise do not have any normal/euploid embryos to transfer. Only 7 cycles from the donor group resulted in cohorts with zero euploid embryos. Conclusion: The ability of PGT-A by NGS to delineate between high-level and low-level mosaic embryos allows patients without euploid embryos for transfer the ability to identify mosaic embryos with the greatest likelihood of producing a successful pregnancy. Approximately 8% of all embryos tested by PGT-A are low-level mosaic, with 16% of cycles without identified euploid embryos producing at least one low-level mosaic embryo. The results herein can be used to counsel patients and guide expectations.